Continuous flow left ventricular assist devices do not worsen endothelial function in subjects with chronic heart failure: a pilot study - Cortese, Francesca; Ciccone, Marco Matteo; Gesualdo, Michele; Iacoviello, Massimo; Frigerio, Maria; Cipriani, Manlio; Giannattasio, Cristina; Maloberti, Alessandro; Giordano, Paola (ESC Heart Failure, 2021)
Aims To evaluate endothelial function in subjects with left ventricular assist devices (LVADs), comparing them with subjects with chronic heart failure with reduced ejection fraction on the list for heart transplant (HT) and with HT patients with a normal systolic cardiac function to identify any differences. Methods We enrolled 28 subjects with LVAD, 55 subjects with HT, and 42 subjects with heart failure on the transplant list. The subjects underwent a general physical examination, assessment of laboratory blood parameters, and assessment of endothelial function through flow‐mediated dilation (FMD) of brachial artery. Results The three groups were homogeneous as regards age, gender, smoke abuse, C‐reactive protein (CRP) and FMD parameters (P = ns). In LVAD group percentage of FMD change showed an inverse correlation with CRP (rho: −0.5, P: 0.003), a well‐known marker of inflammation and tissue damage. Conclusions Continuous flow related to LVAD seems to not worsen endothelial function. Endothelial function was not affected by cardiovascular risk factors (hypertension, hypercholesterolaemia, diabetes, obesity, and tobacco habit), by the functional status expressed by New York Heart Association class, by the left ventricular systolic function and by the presence or absence of ischaemic heart disease in all the populations analysed. CRP was the only factor able to influence percentage of FMD change in patient with LVAD, reinforcing the hypothesis that inflammation is the main determinant of endothelial function.